3+6d=7+6+8d

Simple and best practice solution for 3+6d=7+6+8d equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3+6d=7+6+8d equation:



3+6d=7+6+8d
We move all terms to the left:
3+6d-(7+6+8d)=0
We add all the numbers together, and all the variables
6d-(8d+13)+3=0
We get rid of parentheses
6d-8d-13+3=0
We add all the numbers together, and all the variables
-2d-10=0
We move all terms containing d to the left, all other terms to the right
-2d=10
d=10/-2
d=-5

See similar equations:

| 7+4y=-5,y= | | 8x−5=10x−7 | | 6z-3z-1=2z+7 | | 8x-5=10x-78x−5=10x−7 | | 11/5y-3=-2 | | 11-4x-7-6=6 | | 24=33+x | | 12x-15=3(2x+13) | | x+16+x=21 | | -2(8-3h)=2(-6+4h) | | 20x+16=21 | | -5(2+3x)-4x=28 | | |x+2|=|2x+6|+1 | | -8g-1=-9g+9 | | 3(r−6)=9 | | 5(4x+9)=-26+51 | | 2g+2.6=18.6 | | 7.2=0.2m | | 4x+8=−1x−9 | | -19x—34=55—x | | 2p-4.2=1.8 | | 6(2x+6)-5=-5 | | 8n-5-1=-15+9n | | m-5.2/3=2.7 | | 17x+3⋅(x-1)=57 | | 1/2(2/3e-3+2e)=-4(1/8e+1-e) | | 56s^{2}+31s+3=0 | | 4(x+3)-9(x-2)=10 | | 5w-125=60 | | -10v=-6-8(v-2) | | 5y−4=11 | | x+-42=30 |

Equations solver categories